EFFECT OF MEDIA AND HORMONES ON ROOTING OF AFRICAN MARIGOLD STEM CUTTINGS IN MIST CHAMBER - D. APARNA*, M. L. N. REDDY, A. V. D. DORAJEE RAO, V. V. BHASKAR, P. SUBBARAMAMMA and K. UMA KRISHNA (The Journal of Research ANGRAU, 2021)
Experiments conducted from 2017 to 2019 (to find out suitable media and hormones for betterrooting and establishment of marigold terminal cuttings for summer cultivation) revealed that cocopeatamong media and IBA @ 3000 ppm as powder among hormonal treatments are the best which recordedhighest percentage of rooted cuttings (75.00%, 95.10% ), highest number of roots per cutting (122.68,174.90 ), maximum survival percentage of rooted cuttings (77.96%, 96.62% ), root length (4.64 cm,5.62 cm ) and percentage establishment of rooted cuttings in main field (76.03%, 95.58%), respectively.Among the interaction effects, cocopeat and IBA @ 3000 ppm as powder recorded the maximumvalues for percentage of rooted cuttings (98.00%), number of roots per cutting (174.90), primaryroots per cutting (11.58), secondary roots per cutting (114.6), longest root (5.62 cm), fresh weight ofroots (1.68 g), dry weight of roots (0.60 g), root to shoot ratio (1.25), survival percentage of rootedcuttings (96.62%) and percentage establishment of rooted cuttings in main field (95.58 %). Whereas,cocopeat, NAA 200 ppm and their combination recorded the maximum shoot length (16.07 cm, 22.86cm and 23.49 cm ) and highest number of leaves per rooted cutting (153.73, 184.80 and 197.55),respectively. The lowest values for all the parameters were recorded in sand medium alone withoutany hormonal treatments.